2020
DOI: 10.21873/invivo.12145
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Review and Meta-analysis of Impact of Splenectomy for Advanced Gastric Cancer

Abstract: Background/Aim: Prophylactic splenectomy has shown no inferiority for tumors not invading the greater curvature side. Despite this, the clinical impact of prophylactic splenectomy for proximal advanced gastric cancer is not clear. This review aimed to clarify the impact of splenectomy for advanced gastric cancer in the upper third of the stomach. Materials and Methods: A systematic review and metaanalysis were conducted based on PubMed and EMBASE databases. The following search terms were used: "gastric cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
2
0
0
1
Order By: Relevance
“…Our study found gastric cancer patients in splenectomy group showed a signi cantly higher hospital mortality than no splenectomy group because our research including more studies. Regarding to postoperative complication, most meta-analysis demonstrated that gastrectomy with splenectomy had signi cantly higher incidence of postoperative complications, which was consistent with our results [13,14,119,123,124]. Previous meta-analysis found that the incidence rate of postoperative complications, including PSVT and pancreatic injury, was signi cantly higher in the splenectomy group [15].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study found gastric cancer patients in splenectomy group showed a signi cantly higher hospital mortality than no splenectomy group because our research including more studies. Regarding to postoperative complication, most meta-analysis demonstrated that gastrectomy with splenectomy had signi cantly higher incidence of postoperative complications, which was consistent with our results [13,14,119,123,124]. Previous meta-analysis found that the incidence rate of postoperative complications, including PSVT and pancreatic injury, was signi cantly higher in the splenectomy group [15].…”
Section: Discussionsupporting
confidence: 90%
“…Previous meta-analysis found splenectomy did not increase the mortality of gastric cancer and liver cancer [13,14,16,[119][120][121][122][123][124]. Similarly, our study found there were no signi cant differences in hospital mortality for liver cancer and esophageal and esophago-gastric junction cancer between two groups.…”
Section: Discussionsupporting
confidence: 74%
“…2 cm: endoskopische Resektion >G1 / > 2cm: Gastrektomie + D2-LAD G1, ≤ 1,5 cm: endoskopische Resektion >G1 / > 1,5cm: Gastrektomie + D2-LAD Gastrektomie + D2-LAD Gastrektomie + Systemtherapie, BSC, Gastrektomie +/-Metastasektomie nur als Individualentscheidung Splenektomie oder Pankreaslinksresektion, die in der Studie häufig im Rahmen der D2-LAD durchgeführt wurden, vergesellschaftet. Weitere Studien konnten zeigen, dass eine D2-LAD ohne Pankreaslinksresektion und Splenektomie bei entsprechender chirurgischer Erfahrung die postoperative Mortalität nicht erhöht, sodass empfohlen wird, diese Eingriffserweiterungen nur bei zwingender technischer Notwendigkeit durchzuführen[3,14,15,16].…”
unclassified